Comparative analysis of cast in situ slab method with half slab precast in terms of time and cost on The Kasih Ibu Surakarta Hospital construction project - Mitasari, Agusvivia; Pahang Putra, I Nyoman Dita; Puspitasari, Nia Dwi (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2024)
The development of methods / systems in the field of construction every year is increasing, so that in planning a construction building can choose the most economical, effective, and efficient method to be applied. One of them is the casting implementation method which can be done by conventional method (cast in situ) and precast method (precast). In this study, the object reviewed is the Kasih Ibu Surakarta Hospital Construction Project, where the method of carrying out floor slab casting work uses the cast in situ method which will later be carried out a comparative analysis between the cast in situ method and the half slab precast method in terms of time and cost. This study uses data in the form of shop drawing, RAB, AHSP, and data on the number of workers to be the basis for analysis between the two methods. The results of the comparative analysis of the cast in situ method and the half slab precast method in terms of time and cost obtained results for the cast in situ method plate takes 129.26 days at a cost of IDR 11,200,040,000 while for the half slab precast method plate takes 108.89 days for IDR 2,375,860,000